2017
DOI: 10.1002/term.2420
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(hydroxybutyrate) scaffolds promote engraftment of human skin equivalents via macrophage M2 polarization and angiogenesis

Abstract: Human dermo-epidermal skin equivalents (DE) comprising in vitro expanded autologous keratinocytes and fibroblasts are a good option for massive burn treatment. However, the lengthy expansion time required to obtain sufficient surface to cover an extensive burn together with the challenging surgical procedure limits their clinical use. The integration of DE and biodegradable scaffolds has been proposed in an effort to enhance their mechanical properties. Here, it is shown that poly(hydroxybutyrate) electrospun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…This is a central problem in several soft tissue disorders, including skin, nerve, muscle, ligament, and tendon. [28][29][30][31] For example, depletion of phagocytic myeloid cells before cardiotoxin-induced muscle injury blocked the removal of cell debris and impaired normal muscle regeneration, 32 demonstrating the importance of phagocytic M1 macrophages in the initial stages of muscle regeneration. Controlling the ratio of M1 and M2 macrophages is critical; and modulating these events using galectin-1 could improve healing in muscle and other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This is a central problem in several soft tissue disorders, including skin, nerve, muscle, ligament, and tendon. [28][29][30][31] For example, depletion of phagocytic myeloid cells before cardiotoxin-induced muscle injury blocked the removal of cell debris and impaired normal muscle regeneration, 32 demonstrating the importance of phagocytic M1 macrophages in the initial stages of muscle regeneration. Controlling the ratio of M1 and M2 macrophages is critical; and modulating these events using galectin-1 could improve healing in muscle and other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…When treating deep wounds in porcine models, the hydrogel treatment showed full regeneration of skin with a reduction in fibrosis and the regenerated skin retains a reticulated endothelial layer. In another study, Castellano et al showed a significant reduction in the M1/M2 ratio of biopsied tissue of mice implanted with electrospun poly (hydroxybutarate) (PHB) scaffolds when compared to MatriDerm® and PCL implants (Figure 6C ; Castellano et al, 2018 ). The implant developed in this study was a dermo-epidermal skin equivalent in which human fibroblasts or endothelial cells were seeded and grown in the scaffold before xenograft implantation onto mice.…”
Section: Immunomodulatory Biomaterials For Skin Tissue Engineeringmentioning
confidence: 93%
“…The use of immunomodulatory biomaterials in an implant localizes immunosuppression to the wound site by removing the need for immunosuppressive drugs while having the potential to further reduce poor cosmetic outcomes. Common strategies in immunomodulation for skin regeneration include macrophage polarization (Sun, 2017 ; Castellano et al, 2018 ), the use of glycosaminoglycans (GAGs) (Bhowmick et al, 2017 ; Pezeshki-Modaress et al, 2017 ), and the use of decellularized matrices (Kuna et al, 2017 ).…”
Section: Immunomodulatory Biomaterials For Skin Tissue Engineeringmentioning
confidence: 99%
“…Os materiais sintéticos são utilizados em feridas de alta contaminação por serem menos propensos a ação dos microrganismos. Porém o tempo de cicatrização se eleva, pois, ele demora cerca de duas semanas a mais para a vascularização ser suficiente a ponto de permitir a migração e manutenção da vida celular, portanto a avaliação de utilização vai depender do médico que realizará o tratamento (BOYCE; LALLEY, 2018;CASTELLANO et al, 2017)…”
Section: Scaffolds Biológicos E Sintéticos Usados Em Engenharia Deunclassified